Collaborative Governance dalam Program Sanitasi Total Berbasis Masyarakat (STBM) - Wida Indrayanti; Siti Aisyah; Sri Sediyaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the role of traditional villages in collaborative governance in the Community-Based Total Sanitation Program (STBM) in Tabanan Regency, especially to accelerate the achievement of stop open defecation (SBS) status. Descriptive qualitative methods were used in this study. Locations and informants were selected by purposive sampling. The results of the study indicate that collaborative governance that runs well at the Tabanan Regency level, Selemadeg District, and Wanagiri Kauh Village, is supported by trust, shared commitment, customary regulations (awig-awig/pararem), and synergy between community elements. This collaboration accelerates the achievement of SBS status in the area. On the other hand, in Penebel District and Babahan Village, collaboration with traditional villages has not been optimally formed so that program achievements are slower. Based on the results of the study, it was found that collaborative governance in the program is in accordance with the theory of Ansell and Gash. Indigenous villages play an important role in the pre-triggering, Community Led Total Sanitation (CLTS) triggering and post-triggering process, thus accelerating the achievement of ODF status in an area. Keywords: Collaborative Governance, Indigenous Village’s Role, Program Implementation